TINJAUAN IMPLEMENTASI PEMADANAN NIK MENJADI NPWP (STUDI KASUS PADA KPP PRATAMA SUKOHARJO) - Dokza Equaristo; Meka Sabilla Salim (Bajang Institute, 2025)
This research aims to review the implementation of NIK-NPWP matching at KPP Pratama Sukoharjo in accordance with Minister of Finance Regulation Number 136 of 2023 concerning Amendments to Minister of Finance Regulation Number 112/PMK.03/2022 by considering the principle of simplicity and the principle of adaptability. The type of research used is descriptive research. The data collection techniques used include interviews with functional extension workers and Account Representatives, observation, documentation, and conducting online surveys. The results obtained from this research have provided several conveniences for Taxpayers and the Government in the effort towards Satu Data Indonesia